Applications of 3D Printing in Pediatric Dentistry: A Literature Review - Marwa Basim; Ali R. Al-Khatib; Zainul A. Rajion (University of Mosul, College of Dentistry, 2024)
There are many challenges facing Pediatric dentists while treating children, because they have lots of anxiety and fear with dental treatment, as they are emotionally immature. Nowadays shifting of pediatric dentistry is towards advanced dental treatment for superior and precise performance. Amongst these advancements, the concept of 3D printing has recently emerged. Dental professionals and patients have many benefits from the use of 3-D printing technology. This review highlights the applications of modern digital technologies such as 3D printing in pediatric dentistry for efficient implementation, as well as shows the benefits and constraints of using this technology.